A New Framework for Quantum Image Processing and Application of Binary Template Matching - Yetis, Hasan; Karakose, Mehmet (Institute of Electrical and Electronics Engineers Inc., 2022)
Quantum computing is promising for image processing applications with its parallel processing capability. Today, studies are carried out to perform various image processing operations via quantum computing. In this study, a framework for window-based image processing is proposed. After encoding input images, the proposed framework keeps all the values in the relevant window in separate registers, depending on the window size. Window-based operations can be performed in parallel by applying Hadamard gate to the inputs and performing the related operations on the values in the window. The proposed framework is applied for image matching applications, which is an important branch of image processing. By comparing the searched pattern with the values in the window, it is checked whether it matches the searched pattern. Binary values are used to make the application more understandable. © 2022 IEEE.
26th International Conference on Information Technology, IT 2022 -- 16 February 2022 through 20 February 2022 -- Zabljak -- 178277
Keywords: Image coding; Quantum computers; Binary template matching; Image applications; Image processing applications; Images processing; Parallel processing; Processing capability; Processing operations; Quantum Computing; Quantum image processing; Window-based image processing; Template matching